A thermophile Hydrogenibacillus sp. strain efficiently degrades environmental pollutants polycyclic aromatic hydrocarbons. (23rd December 2021) - Qiu, Xiaoyu; Wang, Weiwei; Zhang, Lige; Guo, Lihua; Xu, Ping; Tang, Hongzhi
Summary: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous pollutants threatening ecosystems and human health. Here, we isolated and characterized a new strain, Hydrogenibacillus sp. N12, which is a thermophilic PAH‐degrader. Strain N12 utilizes naphthalene as a sole carbon and energy source above 60°C and co‐metabolizes many other PAHs as well. The metabolites were identified in the catabolism of naphthalene by gas chromatography–mass spectrometry (GC–MS) and stable isotopic analysis. Based on the identified metabolites, we proposed two possible metabolic pathways, one via salicylic acid and the other via phthalic acid. Whole‐genome sequencing reveals that strain N12 possesses a small chromosome of 2.6 Mb. Combining genetic and transcriptional information, we reveal a new gene cluster for the naphthalene degradation. The genes, designated as nar AaAb that are predicted to encode the alpha and beta subunits of naphthalene dioxygenase, were subsequently subcloned into Escherichia coli and the enzyme activity was detected by whole‐cell transformation. Capacity to degrade several other tricyclic‐PAHs was also characterized, suggesting co‐existence of other constitutively expressed enzyme systems in strain N12 in addition to the naphthalene degradation gene cluster. Our study provides insights into the potential of the thermophilic PAH‐degrader in biotechnology and environmental management applications.